2010
DOI: 10.1166/jbn.2010.1143
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Inorganic Nanoparticles and Cosmetics: Facts, Issues, Knowledge Gaps and Challenges

Abstract: The cosmetic industry is among the first adaptors of nanotechnology through the use of engineered nanoparticles (ENPs) to enhance the performance of their products and meet the customers' needs. Recently, there have been increasing concerns from different societal stakeholders (e.g., governments, environmental activist pressure groups, scientists, general public, etc.) concerning the safety and environmental impact of ENPs used in cosmetics. This review paper seeks to address the twin concerns of the safety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 67 publications
0
73
0
2
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, cosmetic application of nanoparticles is regarded as the best technology to upgrade the performance of cosmetic products and to meet the consumer's needs. 19 For example, Popov et al showed that potential application of zinc oxide or titanium oxide nanoparticles for sunscreen has benefit to attenuate ultraviolet light by absorption and scattering. 20 Furthermore, the effect of particle size on the potential of titanium oxide nanoparticles as a sunscreen was also reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, cosmetic application of nanoparticles is regarded as the best technology to upgrade the performance of cosmetic products and to meet the consumer's needs. 19 For example, Popov et al showed that potential application of zinc oxide or titanium oxide nanoparticles for sunscreen has benefit to attenuate ultraviolet light by absorption and scattering. 20 Furthermore, the effect of particle size on the potential of titanium oxide nanoparticles as a sunscreen was also reported by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has been done regarding hazards following from dermal exposure to coated TiO 2 nanoparticles which show at least some photocatalytic activity [7,109,[118][119][120]. This photocatalytic activity gives rise to the generation of reactive oxygen species.…”
Section: Human Health Hazards Following From Dermal Exposure To Persimentioning
confidence: 99%
“…Barnard [7] has suggested that the per particle hazard of TiO 2 nanoparticles linked to the generation of reactive oxygen species under irradiation by sunlight has a maximum at *33 nm. It may well be that smaller nanoparticles are more likely to breach the barrier of the stratum corneum than larger nanoparticles [120]. Following breaching of the stratum corneum, effects may be based on interaction with antigen presenting cells [117] and the molecular mechanisms discussed before, such as the generation of reactive oxygen species and interaction with cellular components such as proteins [1][2][3][96][97][98][99], and references therein].…”
Section: Human Health Hazards Following From Dermal Exposure To Persimentioning
confidence: 99%
See 2 more Smart Citations